Penerapan Open Government Dalam Meningkatkan Kualitas Informasi Publik di Kota Denpasar: (Kajian Denpasar Open Data) - Adi Sastra Wijaya, Komang Adi; Lukman, Juwita Pratiwi; Sinta Dewi, Sang Ayu Nyoman; Riani, Ni Wayan (Jayapangus Press, 2025)
The open government concept has been implemented in Denpasar City based on Denpasar Mayor Regulation Number 28 of 2011 concerning Guidelines for Management of Information and Documentation Services in the Denpasar City Environment. One of them is through the Denpasar Open Data website which supports easy access to information for the public regarding the city of Denpasar. The application of the open government concept in Denpasar City in monitoring and evaluating government openness instruments is considered inadequate so it must be considered optimally. Apart from that, there is invalidity of data sources, thereby reducing public trust. The aim of this research is to analyze the application of open government in improving public services in Denpasar City based on the Denpasar Open Data study. The research method used is qualitative with a descriptive approach. Data collection techniques through observation, interviews and documentation. Research data analysis using Miles and Huberman consists of data reduction, data presentation, and drawing conclusions. The research results show that the implementation of open government in Denpasar City has gone well, but there are several obstacles found on the main website in facilitating public participation. There are several platforms that do not provide public access to data so they need to be optimized by the Denpasar City Communications, Information and Statistics Department to meet the needs of the community.